Effects of tualang honey supplementation on haematological parameters and oxidants/antioxidants level in erythrocytes of rats exposed to petrol vapours - Abubakar, Murtala Bello (2013)

(untitled)
Petrol is used as fuel for internal combustion engines. Different health risks including weight loss, haematotoxicity, and oxidative stress have been reported for gasoline. Supplementation with antioxidants such as vitamins A, C, and E has been shown to ameliorate the toxicity effects of gasoline vapours exposure. Honey is a natural product which contains vitamins and polyphenols that possess good antioxidant properties. The present study was carried out to determine the potential protective role of honey against the adverse effects of exposure to gasoline on weight gain, haematological parameters, bone marrow cytology, and oxidants/antioxidants status in erythrocytes of rat. A total of 56 male Sprague-Dawley rats (aged 6-7 weeks, 170-230g) were used in the study. Six rats were used for phase 1 and were randomized and treated as control (exposed to ambient air daily, n=3) and gasoline exposed (exposed to gasoline vapours 11.13±1.1cm3/h, 6h daily, 6 days/week, n=3) groups. Body weight was monitored weekly and blood sample for full blood count (FBC) and differential counts (DC) was collected at 4th, 6th, 8th, 10th, and 11th week duration. At the end of this phase, the rats were sacrificed and bone marrow was extracted, smeared and stained for cytology. Fifty rats were used for phase II and randomized into five groups (10 per group) and treated for 11 weeks as follows: Normal control group (NCG) - treated with 0.5ml distilled water and exposed to ambient air daily, experimental petrol control group (EPG) - exposed to gasoline + distilled water as above, honey control group (HCG) - treated with honey 1.2g/kg body weight daily, experimental honey test group (ETG-1)- exposed to gasoline and concurrently treated with honey as above, and experimental honey test group-2 (ETG-2) - exposed to gasoline as above and treated with honey during the last two weeks of the experiment. Weight gain was monitored weekly and at the end of experimental period, blood sample for FBC + DC and oxidative markers was collected via cardiac puncture; and bone marrow was extracted for cytology. The result of phase I established that significant alterations in weight gain and haematological parameters appeared in the gasoline exposed group on the 10th week. The results of phase II showed that exposure to gasoline was associated with significant (p<0.05) impairment of weight gain and reduction in mean corpuscular haemoglobin concentration (MCHC) as well as higher percentage of abnormal megakaryocytes. Honey supplementation significantly improved the percentage of abnormal megakaryocytes but did not improve the weight gain and MCHC values. In addition, exposure to gasoline did not cause significant changes in oxidative markers. In conclusion, this study indicates that exposure to gasoline caused adverse effects on weight gain, blood cell indices and bone marrow megakaryocytes; and that supplementation with honey has the potential to protect against some of the adverse effects.